Nontargeted lipidomic characterization of porcine organs using hydrophilic interaction liquid chromatography and off-line two-dimensional liquid chromatography-electrospray ionization mass spectrometry - Cífková, Eva; Holčapek, Michal; Lísa, Miroslav (Lipids, 2013)
Lipids form a significant part of animal organs and they are responsible for important biological functions, such as semi-permeability and fluidity of membranes, signaling activity, anti-inflammatory processes, etc. We have performed a comprehensive nontargeted lipidomic characterization of porcine brain, heart, kidney, liver, lung, spinal cord, spleen, and stomach using hydrophilic interaction liquid chromatography (HILIC) coupled to electrospray ionization mass spectrometry (ESI/MS) to describe the representation of individual lipid classes in these organs. Detailed information on identified lipid species inside classes are obtained based on relative abundances of deprotonated molecules [M-H](-) in the negative-ion ESI mass spectra, which provides important knowledge on phosphatidylethanolamines and their different forms of fatty acyl linkage (ethers and plasmalogens), phosphatidylinositols, and hexosylceramides containing nonhydroxy- and hydroxy-fatty acyls. The detailed analysis of identified lipid classes using reversed-phase liquid chromatography in the second dimension was performed for porcine brain to determine more than 160 individual lipid species containing attached fatty acyls of different acyl chain length, double-bond number, and positions on the glycerol skeleton. The fatty acid composition of porcine organs is determined by gas chromatography with flame ionization detection after the transesterification with sodium methoxide.
Keywords: játra; Chromatography, Liquid; Spinal Cord; Hydrophobic and Hydrophilic Interactions; Fatty Acids; Stomach; ledviny; Phosphatidylethanolamines; fosfatidylethanolaminy; Lung; lipidy; mícha; Kidney; zvířata; plíce; plasmalogeny; Swine; hmotnostní spektrometrie s elektrosprejovou ionizací; Brain Chemistry; mozek - chemie; Chromatography, Gas; mastné kyseliny; Plasmalogens; Liver; chromatografie kapalinová; Phospholipids; žaludek; Spleen; Lipids; myokard; fosfolipidy; Spectrometry, Mass, Electrospray Ionization; Animals; Myocardium; chromatografie plynová; prasata; hydrofobní a hydrofilní interakce; slezina